Clima laboral y el estrés en trabajadores de una empresa importadora del cantón El Empalme - Guerrero Salinas, Johanna Lizabeth (2022)
The present study was conducted with the aim of analyzing the influence of the work climate on stress in workers working in an importer located in the canton El Empalme, belonging to the province of Los Ríos, Ecuador.Three purposes were proposed which were to conceptualize the work climate and stress through the bibliographic study of several authors, a second purpose was to identify through information gathering tools the characteristics of the work climate and stress and finally it was intended to describe the incidence of the work climate on the stress of workers of an importing company of the canton El Empalme. The theoretical framework refers to theories and criteria regarding the research variables: Work climate and stress. The hypothesis of this research work questions whether the importing company Alonzo maintains a working climate that affects the generation of workers' stress. The type of research is nonexperimental and correlative in addition to employing a quantitative approach, The research was developed with the collaboration of 25 employees belonging to the company and resulted in low levels on the scale that qualifies the work climate that define it as authoritarian, as well as high levels of work stress. Concluding that if there is an inversely proportional relationship between the authoritarian and inadequate work climate present in the institution and the high levels of general work stress revealed by its employees and recommending that workshops be applied to improve management organizational and leadership.